(untitled) (Research, Society and Development, 2025)
Acrobustitis is an inflammatory disease that affects the prepuce of male cattle and may progress to severe complications such as obstructive urolithiasis. This study aims to report a case of chronic acrobustitis with urethral obstruction in a Senepol bull treated by partial penectomy associated with urethrostomy. The three-year-old animal was examined on a rural property in Espigão do Oeste, Rondônia, presenting with a swollen and edematous preputial region, pain on palpation, and difficulty urinating. After clinical evaluation, surgical intervention was performed, consisting of partial removal of the penis and creation of a new urethral opening to reestablish urinary flow. The procedure was effective, allowing clinical recovery and maintenance of the animal’s condition for fattening until slaughter. This case highlights the importance of early diagnosis, proper surgical technique selection, and postoperative care to ensure animal welfare and survival in bovines affected by genital and urinary disorders.